Benzoyl Peroxide Inhibits Quorum Sensing and Biofilm Formation by Gardnerella vaginalis 14018. (2nd July 2018) - Algburi, Ammar; Zehm, Saskia; Netrebov, Victoria; Weeks, Richard; Zubovskiy, Konstantin; Chikindas, Michael L.
Abstract : Infection recurrence and antibiotic resistance of bacterial vaginosis-associated pathogenic biofilms underline the need for novel and effective treatment strategies. In this study, we evaluated the antimicrobial, antibiofilm, and quorum sensing inhibitory effects of benzoyl peroxide and salicylic acid against Gardnerella vaginalis ATCC 14018, the predominant pathogen of bacterial vaginosis. While the highest tested concentrations of 250 and 125 μ g/mL for both compounds were not sufficient in completely inhibiting the growth of G. vaginalis ATCC 14018, they did prevent biofilm formation by inhibiting the bacterial quorum sensing system in the pathogen. To our knowledge, this report is the first evidence that benzoyl peroxide can have a quorum sensing-mediated biofilm controlling effect, as demonstrated using subinhibitory concentrations of this compound in order to reduce the cost, dosage, and negative side effects associated with current antimicrobial treatments.